President Prabowo's Political Communication on Environmental Issues in Constructing Climate Narrative - Bakti Abdillah Putra (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2025)
President Prabowo Subianto officially won presidential election in 2024 and began his administration effectively in October. He had some plans and policies to support national development, including food security and the expansion of palm oil plantation. These sectors are against ecosystem conservation and climate change prevention so that the issue became a controversy among the people. Through his official speech, President Prabowo did not mention environmental issue, whereas he put other sectors as top priorities. Media caught the event and and public paid attention as well. This research aims to analyze the framing on President Prabowo's political communication regarding environmental issue. The analysis was conducted with framing theory of Robert N. Entman including his four main components, define problems, diagnose causes, moral judgement, and treatment recommendation. Two media which were observed by the researcher are Tempo.co and Betahita.id with qualitative approach. Researcher also applied Agenda Setting theory with critical discourse approach to see how media perceive the President in addressing the weakness in governance and lacking of relevant knowledge. Meanwhile, Betahita.id assessed that President Prabowo's narrative on environmental issue is a form of his carelessness towards human rights issues and his partiality with irresponsible corporations.